World economic outlook : a survey by the staff of the International Monetary Fund - International Monetary Fund (Washington, D.C International Monetary Fund (IMF), 1987)
​The World Economic Outlook (WEO) is a survey conducted and published by the International Monetary Fund. ... WEO forecasts include key macroeconomic indicators, such as GDP, inflation, current account and fiscal balance of more than 180 countries around the globe. It also deals with major economic policy issues
Frequency varies from 1998-1998 frequency annual, from 2000 - frequency semiannual. Some issues also have thematic titles
Keywords: Microeconomics; ECONOMIC DEVELOPMENT; INTERNATIONAL ECONOMIC RELATIONS; ECONOMIC POLICY; ECONOMIC FORECASTS; PERIODICALS; IMF